Epigenetic regulation of innate immunity - Takeuchi, Osamu (Henry Stewart Talks, 2012)
The innate immune cells, Pathogen sensing receptor system, Histone modifications and inflammation control, Critical role of Jmjd3, a trimethyl H3K27 specific demethylase, in M2 macrophage differentiation, Identification of IRF4 as a Jmjd3 target gene inducing M2 macrophages